Pin-on-disc study of brake friction materials with ball-milled nanostructured components. (5th February 2017) - Menapace, Cinzia; Leonardi, Mara; Perricone, Guido; Bortolotti, Mauro; Straffelini, Giovanni; Gialanella, Stefano
Abstract: Copper is an ingredient of the automotive disc brake pads with important functional role. On the other hand, copper is regarded as one of the most hazardous component of the particulate matter released by the brake linings. Legislation in several countries is progressively reducing the tolerated amount of copper in friction materials. In this work, a possible approach to the reduction of copper in brake friction materials is presented. Starting from a commercial, state-of-the art, non-asbestos organic friction material, different formulations have been prepared, changing the microstructure of some of the ingredients, namely copper and zirconia using high energy ball-milling. The wear behavior of the newly developed materials has been tested and validated using pin-on-disc wear tests. One interesting aspect observed is that the wearing out of copper fibres produces fine copper particles entering the friction layer, thus contributing to its compaction. This observation implies that copper powder is not strictly required as a component in the starting friction material to achieve anyway a satisfactory tribological behavior associated with a stable friction layer. Furthermore, the addition of milled components provided interesting indications to be explored further in view of the replacement of copper in brake friction materials. Graphical abstract: Highlights: The role of the copper has been studied with the aim of reducing its concentration in brake friction materials. The design of the friction material was changed introducing two ingredients, nanostructured after ball-milling. Ball milling induced the formation of Cu-ZrO2 clusters that influence the tribological behavior of the new materials. Even in the absence of copper particles, a good friction layer is formed thanks to the wearing of copper fibers.